Estudo magnetotelúrico na região centro-sul da província Borborema – Caçapava do Sul, RS - (:unkn) unknown (Universidade Federal do Pampa, 2017)
The Magnetotelluric method (MT), a geophysical method of passive electromagnetic polling, is an alternative for the study of the geologic outline, used more and more for this objective.Therefore, the present work proposes a magnetotelluric study of the subsurface of the south-central region of the Borborema Province to obtain the geoelectric parameters of the crust. The motivation for this work lays on the tectonic complexity in which the formation of Borborema province occurred, further on the rare information about it limits in subsurface. For the realization of this study, magnetotelluric data from 33 stations, placed in a semi linear profile, obtained through project “Estudo da estrutura da litosfera do Nordeste do Brasil” (MCT/CNPq, 573713/2008-1), made available by the “Instituto Nacional de Pesquisas Espaciais (INPE)” was used. The processing of this data used advanced technics, available for the community of electromagnetics studies in the earth core and presented in the form of pseudosections. The pseudosections consist of sections of the components of the tensor impedance as a function of the signal period and suggest a geoelectrically heterogeneous subsurface with very resistive structures except in the regions of the Jatobá and Rio Peixe sedimentary basins and in the sub domain Alto Pajeú and Cabrobó that have conductive anomalies. These conductive anomalies in the regions of the sedimentary basins are correlated with the sedimentary package already mapped in these areas and the conductive anomalies in the subdomain Alto Pajeú and Cabrobó arranged in the data present an uncertain origin.
Keywords: Província Borborema; Magnetotelúrico; Processamento; Borborema Province; Magnetotelluric; Processing; CNPQ::CIENCIAS EXATAS E DA TERRA